ZINC OXIDE NANOPARTICLES AS ADDITIVE TO ENHANCE THE SOLID-STATE EMISSION OF A HETEROLEPTIC Cu(I) COMPLEX - Paulina Dreyse; Daniel Navas; Santana Camila; Mireya Santander-Nelli; Luis Sanhueza; Andrés Ibañez (Journal of the Chilean Chemical Society, 2025)
The synthesis and characterization of Zinc Oxide Nanoparticles (ZnO NPs) is reported at 0°C and room temperature, with 1–octadecanol, zinc acetate and lithium hydroxide. The ZnO structural and electronic nature was confirmed by Transmission Electron Microscopy, powder X-Ray Diffraction and UV-Vis absorption. NPs exhibited diameters within 8 – 13 nm and ellipsoidal morphology.The synergism between the ZnO NPs on the luminescent response of a Cu(I) complex in solid-state by stacking layers on a glass substrate was evaluated. Main results show that the complex increases emission response by 2.45 compared to the absence of the ZnO NPs layer. This behaviour could be interpreted by a possible energy transfer due to the interaction between the optical band gap of ZnO NPs semiconductor with the emitting Cu(I) complex. Despite the observed behavior appears as preliminary results (a systematic study of each coating layers must be clarified), the observed luminescent response on the coated glass was consistent with the large emissive response due to the interacting ZnO NPs with the heteroleptic Cu(I) complex. These results appear as outstanding to the future performance hybrid material using nanomaterials to enhance the luminescence of non-expensive metal for optical applications.